Sasterawan negara di takhta keunggulan - Mana Sikana, 1945- (Kuala Lumpur : Institut Terjemahan dan Buku Malaysia, 2015)
On history and criticism of Malay literature.
Includes bibliographical references.
In Malay.
Keywords: Malay literature -- History and criticism; Authors, Malay -- Malaysia